2021
DOI: 10.1002/jmv.27453
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and analysis of potential risk factors of high‐risk human papillomavirus (HPV) in Shanghai China: A cross‐sectional one‐year study in non‐vaccinated women

Abstract: Data regarding human papillomavirus (HPV) prevalence, its associated risk factors, and women's knowledge about this disease before the HPV vaccine was approved are limited in Shanghai, China. Therefore, we investigated these questions among females in Shanghai and aimed to provide comprehensive data to guide HPV vaccination and present the biopsychosocial risk factors that impact high-risk HPV infection, and evaluate the level of knowledge and awareness of this disease among women aged

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 43 publications
3
11
0
Order By: Relevance
“…Consistent with other studies ( Niu et al, 2022 ), the current study shows that women with a high school education or lower, have a higher risk of HPV infection than women with a higher education level. Additionally, socioeconomic status is closely related to the incidence of cervical cancer, particularly in developing countries.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with other studies ( Niu et al, 2022 ), the current study shows that women with a high school education or lower, have a higher risk of HPV infection than women with a higher education level. Additionally, socioeconomic status is closely related to the incidence of cervical cancer, particularly in developing countries.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, although the total positivity rate of HPV infection in China is ∼21.69%, it varies between economically developed and underdeveloped areas. For instance, a study in Shanghai included 6,619 women, of whom the HR-HPV infection rate was 9.5% ( Wang et al, 2021 ), whereas another study in Jiangsu included 36,500 women and reported a 28.95% HR-HPV infection rate ( Niu et al, 2022 ). Still further, a study in Guangxi from 2016 to 2021 included 41,140 women, for whom the overall HR-HPV infection rate was 18.10% ( Wei et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are compatible with those reported in the literature. 25 Similar to a previous study, 27 in our study, unmarried individuals were 4.48 times more likely to be HR-HPV-positive than those who were married. It should also be taken into account that singles can have multiple partners.…”
Section: Discussionsupporting
confidence: 88%
“…HR-HPV prevalence rate in our study was 11.65%, which was 2.78 times the prevalence for LR-HPV infection and consistent with a recent national investigation in 2017 (12.1%) [ 27 ], lower than that in Jiangxi (19.53%) [ 28 ] and Shandong (24.2%) [ 29 ]. It is generally believed that the oncogenic HPV infection rate in developed economic areas was lower than in relatively underdeveloped areas [ 30 ]. The feasible reason for the lower HR-HPV prevalence rate in our study may be also associated with relatively developed economy and people,s advanced and better health awareness in Shanghai.…”
Section: Discussionmentioning
confidence: 99%